Real-world evidence from a multi-center pediatric network: greenness exposure and autism spectrum disorder in urban China - Yang, Wenxu; He, Shiwen; Zuoqiu, Sophia (Frontiers in Public Health, 2025)
IntroductionChildhood autism spectrum disorder (ASD) is a global public health concern and its prevalence is increasing rapidly in developing countries such as China. The mechanism behind ASD development remains unclear. Greenness exposure is reportedly associated with various health outcomes, however, the connection between greenness exposure and ASD is relatively unexplored.MethodsWe designed a two-stage screening process and conducted city-wide screening for early childhood ASD to investigate the association between greenness exposure and ASD prevalence in a megacity in southwest China.ResultsWe screened 13,458 children from 0–52 months through 20 local primary care hospitals and the estimated ASD prevalence was 0.55%. We matched greenness exposure, air pollution exposure, and weather condition with ASD diagnosis outcomes based on the study subject’s geographic information. Gender (male) and age (older) were significantly associated with higher odds of being diagnosed with ASD.DiscussionAlthough the association between ASD diagnosis and greenness was not statistically significant, real-world data may help improve ASD screening methods and guide future studies. Our findings highlight the potential role of real-world environmental and health data in informing sustainable urban and pediatric health policies.